From UV to Near-Infrared, WS2 Nanosheet: A Novel Photocatalyst for Full Solar Light Spectrum Photodegradation - Sang, Yuanhua; Zhao, Zhenhuan; Zhao, Mingwen; Hao, Pin; Leng, Yanhua; Liu, Hong (Advanced materials (Weinheim), 2015)
Narrow‐bandgap semiconductor WS2 nanosheets are active photocatalysts, either under visible or under NIR irradiation. The photocatalyst functions are confirmed via photogeneration of an electron‐hole pair, with a low rate of recombination.